Derivatives usage and corporate value on palm oil companies: Moderating roles of corporate governance and business sustainability initiatives - ., Fenny (2020)
Despite the well-established theories pertaining to derivatives use and corporate value, yet the critical question is whether the use of derivatives instruments provides added value for firms. The empirical literature in this area of study has been inconclusive. While prior studies involved non-financial firms and some specific industries (oil and gas, airline, mining, utilities) as their samples, this study complements the literature by exploring palm oil industry, as it has been noted that this industry is distinguished by its rising demand in the market, yet the price of its commodity has declined substantially. Furthermore, social and environmental issues have been greatly debated in this industry in the context of business sustainability and sustainable development. At the same time, the use of derivatives should be unremarkable as palm oil businesses deal with export, they are exposed to the movement in foreign currency exchange rate. In addition, the industry also encounters frequent price fluctuation in the commodity of palm oil. Therefore, this brings upon the question on how prevalence the use of derivatives in creating value for the palm oil firms.